ChemInform Abstract: Structural and Electric Evidence of Ferrielectric State in Pb2MnWO6 Double Perovskite System. Issue 49 (9th December 2014) - Orlandi, Fabio; Righi, Lara; Cabassi, Riccardo; Delmonte, Davide; Pernechele, Chiara; Bolzoni, Fulvio; Mezzadri, Francesco; Solzi, Massimo; Merlini, Marco; Calestani, Gianluca
Abstract The new title compound is prepared by solid state reaction of a stoichiometric mixture of PbO, MnCO3, and WO3 (N2 stream, 800 °C for 2 h and 820 °C for 4 h).